(untitled) - Isaiah Berlin (Oxford, 1978)
The book presents a view of Marx which is both sympathetic and detached. It seizes the point of what Marx wrote and did without sharing Marx's illusions
Keywords: communists - biography,marx, karl, 1818-1883